AN ANALYTIC HIERARCHY PROCESS APPLICATION FOR THE BEST DRIVER SELECTION IN UNIVERSITIES - Bülent BAŞARAN; Musa KEVEN (Challenges of the Knowledge Society, 2015)
Drivers are responsible for the safety and timely delivery of passengers and materials. Universities employ a certain number of drivers and this responsibility is true for them as well. University drivers are usually sent to different duties. Not only road, weather and traffic conditions but also size and type of vehicles change in different duties. Some drivers are more appropriate for some duties while some others are not. Evaluation of alternatives and assigning the best driver to a specific duty is very important for designating authority in universities. The aim of this study is to search whether the Analytic Hierarchy Process (AHP) is applicable to such an environment. In order to do this, the criteria that are necessary for driver selection have been specified. Two examples, which can be encountered in a university environment and contain two different duties, have been given. Based on those criteria, four alternative drivers have been evaluated for both examples. Priority orders of those four alternative drivers are different for both examples when looking at AHP results.